The Epstein-Barr Virus Major Tegument Protein BNRF1 Is a Common Target of Cytotoxic CD4(+) T Cells - Adhikary, Dinesh (J Virol, 2020)
Cellular immunotherapy is a proven approach against Epstein-Barr virus (EBV)-driven lymphoproliferation in recipients of hematopoietic stem cells. Extending the applicability and improving the response rates of such therapy demands improving the knowledge base. We studied 23 healthy donors for specific CD4(+) T cell responses against the viral tegument protein BNRF1 and found such T cells in all seropositive donors, establishing BNRF1 as an important immune target in EBV. We identified 18 novel immune epitopes from BNRF1, all of them generated by natural processing of the full-length protein from virus-transformed lymphoblastoid cell lines (LCL). BNRF1-specific CD4(+) T cells were measured directly ex vivo by a cytokine-based method, thus providing a tool to study the interaction between immunity and infection in health and disease. T cells of the cytotoxic Th1 type inhibited the proliferation of autologous LCL as well as virus-driven transformation. We infer that they are important in limiting reactivations to subclinical levels during health and reducing virus propagation during disease. The information obtained from this work will feed into data sets that are indispensable in the design of patient-tailored immunotherapeutic approaches, thereby enabling the stride toward broader application of T cell therapy and improving clinical response rates. IMPORTANCE Epstein-Barr virus is carried by most humans and can cause life-threatening diseases. Virus-specific T cells have been used in different clinical settings with variable success rates. One way to improve immunotherapy is to better suit T cell generation protocols to viral targets available in different diseases. BNRF1 is present in viral particles and therefore likely available as a target for T cells in diseases with virus amplification. Here, we studied healthy Epstein-Barr virus (EBV) carriers for BNRF1 immunogenicity and report our results indicating BNRF1 to be a dominant target of the EBV-specific CD4(+) T cell response. BNRF1-specific CD4(+) T cells were found to be cytotoxic and capable of limiting EBV-driven B cell transformation in vitro. The findings of this work contribute to forwarding our understanding of host-virus interactions during health and disease and are expected to find direct application in the generation of specific T cells for immunotherapy.